Market Value of Growing Stock on Panchayat Lands Planted during 1982-92 in Western Haryana - Rawat, J. K. (Indian Forester, 1997)
In 1993, a survey was carried out of the plantations raised on the panchayat lands during 1982 to 1992 in the seven districts of Haryana. The paper presents a methodology for estimating market value of the plantation and consequently estimates the market value of tree crops growing on the panchyat lands. The paper also critically anlyses the estimated values and gives certain recommendations for better management of these plantations.